Criteria for peanut seed pre-conditioning for the tetrazolium test - Bittencourt, SRM; Vieira, Roberval Daiton [UNESP]; Rodrigues, TJD (Ista, 1997)
The staining pattern of peanut (Arachis hypogaea L.) seeds with a tetrazolium solution was evaluated to determine the adequate conditions of seed quality evaluations. Three seed lots with different vigour levels and similar moisture content were pre-conditioned using the combination of five periods of time (4, 8, 12, 16 and 20 hours) and four temperatures (20, 25, 30 and 35 degrees C) and then exposed to a 1.0% tetrazolium solution for three hours. The moisture content levels of seeds conditioned for 8 hours at the temperatures of 25, 30 or 35 degrees C, for 12 hours at 20 or 25 degrees C and for 16 hours at 20 degrees C, were above 30%. In this range of moisture level, the staining in tetrazolium was clear and uniform, reflecting an appropriate conditioning of the seeds. However, under a practical point of view, the period of 16 hours at 20 degrees C showed to be the best option, since it allows to start the pre-conditioning an late afternoon of one day and submit the seeds for staining in the following morning.